2021
DOI: 10.1007/s10644-021-09341-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of macroeconomic and structural factors on the unemployment of young women and men

Abstract: The presented article follows the research mainstream of econometric analyses focused on the assessment of correlations between youth unemployment rate and market and macroeconomic determinants, including economic growth and productivity of the economy, its structure in terms of NACE Rev.2 sections as well as the labor market tools. The research addresses 28 European Union (EU) countries. The analysis period covers the years 2008–2018. The econometric methods dedicated to panel data were used. The research res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…They indicate that education of good quality and training programs contribute to school-to-work transition. Despite the minor difference in used methods, the results of this study from high school-level perspective are similar and comparable to studies from other CEE countries like Romania or Hungary, but also with Russia (Danacica, 2014;Demidova & Signorelli, 2012) and Western Europe (Bal-Domańska, 2021;Buttler, 2019;Dvouletý et al, 2020) in short-term.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…They indicate that education of good quality and training programs contribute to school-to-work transition. Despite the minor difference in used methods, the results of this study from high school-level perspective are similar and comparable to studies from other CEE countries like Romania or Hungary, but also with Russia (Danacica, 2014;Demidova & Signorelli, 2012) and Western Europe (Bal-Domańska, 2021;Buttler, 2019;Dvouletý et al, 2020) in short-term.…”
Section: Discussionsupporting
confidence: 84%
“…The unemployment rate of high school graduates immediately after graduation depends on the macroeconomic situation (overall unemployment rate and GDP per capita in the region) and quality of education. Studies identified the positive impact of overall unemployment by Bal-Domańska (2021) and Dimian (2011), whilst the negative impact of GDP was identified by studies of Arslan and Zaman (2014), Bal-Domańska (2021), Bayrak and Tatli (2018), Buttler (2019) and Dimian (2011) andTomić (2018). Although according to these studies, it is enough to boost the economic growth to reduce youth unemployment, the reality of many European economies shows that during the economic growth also, other various macroeconomic and non-macroeconomic indicators affect unemployment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The determinants of unemployment have been widely researched and are presented in the literature. Some authors emphasise the role of economic growth and ecenomic productivity and the structure of GDP (Bal-Domańska 2022, p. 1143Panaite, Prohozescu & Pintilescu 2022, p. 3). They find that Okun's law holds true.…”
Section: Unemployment and Its Determinants In Theoretical Contextmentioning
confidence: 99%
“…One of the most important correlations between the macroeconomic situation and the situation of young people on the labour market is its strong reaction to economic shocks and business cycles. Additionally, it is worth emphasising that unfavourable trends in the economy and employment tend to affect young people even more strongly (Bal-Domańska, 2021;Bod'a & Považanová, 2021;Choudhry et al, 2013;Dunsch, 2017;Hutengs & Stadtmann, 2013) and an improvement in the unemployment rate of young people came with a certain delay in relation to the economy (Choudhry et al, 2013). A question arises as to what extent the situation of young people differs from that of adults and how inclusive are national labour markets for young people?…”
Section: Introductionmentioning
confidence: 99%